STRATEGI PEMASARAN INKLUSIF UNTUK MENINGKATKAN PARTISIPASI UMKM PANGAN DALAM PROGRAM MAKAN BERGIZI GRATIS DI JAWA TENGAH - Rohwiyati, Rohwiyati; Supheni, Indrian - (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2025)
This study aims to analyze the effect of inclusive marketing strategies on the participation of food MSMEs in the Free Nutritious Meal Program in Central Java, as well as its impact on the success of the program. A quantitative approach was adopted, involving 170 respondents from food-based MSMEs. Data were analyzed using SEM-PLS to examine validity, reliability, structural relationships, R², f², and Q² values. The results indicate that inclusive marketing strategies have a positive and significant influence on both MSME participation and program success. MSME participation was also found to mediate the relationship between inclusive marketing strategies and the success of the Free Nutritious Meal Program. The R² values show that 58% of MSME participation and 52% of program success are explained by the model. The effect size (f²) falls within the medium to large category, while the Q² values confirm strong predictive relevance. This research highlights the importance of collaboration, market access, empowerment, and innovation in actively involving MSMEs in the provision of nutritious food. The findings offer strategic recommendations for policymakers and stakeholders to strengthen sustainable program implementation.